A correlation between malocclusion complexity with periodontal status - Nugroho, Mahardhika Setya; Krisnawati, Krisnawati; Widayati, Retno; Lesang, Robert (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Malocclusion is the third most common dental problem after caries and periodontal diseases, with prevalence reaching 56% in the world and 89% in Indonesia (2006), respectively. Index of Complexity, Outcome, and Need (ICON) is an assessment tool to measure the necessity, complexity, and success of orthodontic treatment. Although several studies have reported a causal relationship between malocclusion and periodontal disease, the association is still under debate. The aim of this study was to analyze the correlation between malocclusion complexity based on ICON and the periodontal status of patients who underwent orthodontic treatment at the Orthodontic Clinic, Dental Hospital, Faculty of Dentistry, Universitas Indonesia. Material and Method: This was an analytical study with a cross-sectional design. Fifty-four new patients (aged 25-44 years) were included. Patients who had systemic disease, used fixed orthodontic appliance or prosthesis, and had some local factors were excluded. Periodontal status, ICON complexity, study model, and radiographic results were examined and analyzed. An interclass correlation test was carried out to obtain data reliability. Result: the majority of malocclusion complexities based on ICON were mild (46.3%). Periodontal status consisted of Plaque Index (good, 81.5%; moderate, 18.5%), Papillary Bleeding Index (no bleeding, 90.7%; severe bleeding, 1.9%), Clinical Attachment Loss (moderate, 40.7%; severe, 22.2%), gingival recession (mild, 83.3%; severe, 7.4%), periodontal probing depth (moderate, 77.8%; severe, 3.7%), and alveolar bone height (middle third, 53.7%; cervical third, 46.3%). Conclusion: No significant correlation was found between malocclusion complexity based on ICON and periodontal status.